Lupeol restores dopaminergic function by suppressing glial activation in a Parkinson’s disease mouse model - Ahmad, Riaz; Choe, Kyonghwan; Park, Hyun Young; Ahmad, Waqas; Park, Tae Ju; Kim, Myeong Ok (Frontiers in Immunology, 2026)
IntroductionParkinson’s disease (PD) is a progressive neurodegenerative disorder marked by chronic neuroinflammation and loss of dopaminergic neurons. The neurotoxin MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) selectively targets dopaminergic neurons, effectively replicating the pathological features of PD. Lupeol, a natural pentacyclic triterpenoid, has been shown to exhibit neuroprotective properties in various models by reducing oxidative stress, inflammation, and apoptosis. This study aimed to investigate the neuroprotective effects of lupeol in an MPTP-induced mouse model of PD.MethodsMale mice were administered MPTP (30 mg/kg, i.p.) for seven days to induce PD-like pathology. Lupeol (50 mg/kg) was administered as a potential therapeutic intervention. Behavioral assessments were conducted to evaluate motor function. Biochemical analyses were performed to measure dopamine and tyrosine hydroxylase (TH) levels. Immunohistochemical and molecular approaches were used to assess glial activation, oxidative stress, and apoptotic signaling pathways in the substantia nigra pars compacta (SNpc) and striatum.ResultsLupeol treatment significantly improved MPTP-induced motor impairments and restored dopamine and TH levels. Additionally, lupeol reduced neuroinflammation, by decreasing microglial activation, astrocyte reactivity, and lower levels of inflammatory mediators. Oxidative stress markers, including reactive oxygen species (ROS) and lipid peroxidation (LPO), were diminished in SNpc and striatum following lupeol treatment. Furthermore, lupeol upregulated antioxidant defense mechanisms by increasing the expression of Nrf-2 and HO-1. Apoptotic markers, such as Cytochrome C, Bax, and Caspase-3, were downregulated, indicating reduced neuronal apoptosis.ConclusionThe current study suggests that lupeol exerts neuroprotective effects by inhibiting glial cell activation, thereby reducing neuroinflammation, oxidative stress, and apoptosis in an MPTP-induced PD mouse model.